Upaya Yang Dapat Ditempuh Pemerintah Republik Indonesia Dan Malaysia Dalam Menyelesaikan Sengketa Perbatasan Di Laut Sulawesi Ditinjau Dari Perspektif Hukum Laut Internasional - Mahendra Putra Kurnia (Jurnal Risalah Hukum, 2005)
ABSTRACT Indonesia and Malaysia involved on the teritorial waters conflict. After the sovereignty disputes over Sipadan and Ligitan Islands on 2002, nowadays they have a serious conflict in order to determine the sea teritorial border in Sulawesi waters. Malaysia was made a statement that Blok Ambalat is under Malaysian sovereignty, according to the statement, Malaysia Government give a petroleum concession to the Dutch – British Petroleum Company, Shell. Indonesian Goverments raise a protest against Malaysian statement and their action to giving a petroleum concession to the Dutch – British Petroleum Company, Shell. Indonesian Government think that Blok Ambalat is under Indonesian sovereignty. According to article 2 paragraph 3 and article 33 paragraph 1 United Nations Charter, every states shall settle their international diputes by peaceful means such as negotiation, enquiry, mediation, conciliation, arbitration, judicial settlement resort to regional agencies or arranggements or other peaceful means on their own choice. The United Nations Convention On The Law of The Sea 1982 also furnished the settlement of disputes methods. Indonesia and Malaysia could use the UNCLOS 1982 settlement of disputes methods in view that both countries have ratified the convention. Key words : Indonesia, Malaysia, penyelesaian sengketa (settlement disputes), kedaulatan (sovereignty) dan teritorial (teritory).